The Necrotroph Botrytis cinerea BcSpd1 Plays a Key Role in Modulating Both Fungal Pathogenic Factors and Plant Disease Development - Chen, Huchen; He, Shengnan; Zhang, Shuhan; A, Runa; Li, Wenling; Liu, Shouan (Frontiers in Plant Science, 2022)
Botrytis cinerea is a necrotrophic microbe that causes gray mold disease in a broad range of hosts. In the present study, we conducted molecular microbiology and transcriptomic analyses of the host–B. cinerea interaction to investigate the plant defense response and fungal pathogenicity. Upon B. cinerea infection, plant defense responses changed from activation to repression; thus, the expression of many defense genes decreased in Arabidopsis thaliana. B. cinerea Zn(II)2Cys6 transcription factor BcSpd1 was involved in the suppression of plant defense as ΔBcSpd1 altered wild-type B05.10 virulence by recovering part of the defense responses at the early infection stage. BcSpd1 affected genes involved in the fungal sclerotium development, infection cushion formation, biosynthesis of melanin, and change in environmental pH values, which were reported to influence fungal virulence. Specifically, BcSpd1 bound to the promoter of the gene encoding quercetin dioxygenase (BcQdo) and positively affected the gene expression, which was involved in catalyzing antifungal flavonoid degradation. This study indicates BcSpd1 plays a key role in the necrotrophic microbe B. cinerea virulence toward plants by regulating pathogenicity-related compounds and thereby suppressing early plant defense.